Influence of Ni Solute segregation on the intrinsic growth stresses in Cu(Ni) thin films. (1st March 2016) - Kaub, T.M.; Felfer, P.; Cairney, J.M.; Thompson, G.B.
Abstract: Using intrinsic solute segregation in alloys, the compressive stress in a series of Cu(Ni) thin films has been studied. The highest compressive stress was noted in the 5 at.% Ni alloy, with increasing Ni concentration resulting in a subsequent reduction of stress. Atom probe tomography quantified Ni's Gibbsian interfacial excess in the grain boundaries and confirmed that once grain boundary saturation is achieved, the compressive stress was reduced. This letter provides experimental support in elucidating how interfacial segregation of excess adatoms contributes to the post-coalescence compressive stress generation mechanism in thin films. Graphical abstract: Cu(Ni) film stress relationship with Ni additions. Atom probe characterization confirms solute enrichment in the boundaries, which was linked to stress response.